2011
DOI: 10.1007/s00520-011-1352-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of stem cell transplant recipients receiving glucocorticoid therapy to an exercise-based rehabilitation program

Abstract: The high acuity of hematopoietic stem cell transplant (HSCT) recipients receiving glucocorticoid (GC) therapy for acute graft vs. host disease (aGVHD) may limit their adherence to an exercise-based rehabilitation program and hence, slow their recovery. To make this determination, the medical records of 59 subacute outpatient stem cell transplant recipients receiving methylprednisolone (MP) were reviewed for demographic, anthropometric and medical information. Performance on the repeated sit-to-stand, 50-ft wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
10
2
Order By: Relevance
“…Functional capacity was evaluated using the 6-min walk test, 50-foot walking time, and repeated sit-to-stand movement. While one study reported no significant increase in functional capacity after physical exercise intervention [24], several other studies described a significant increase in functional capacity among the physical exercise group compared to the control group, following physical exercise intervention [11,12,21,22]. In our study, we showed that the highfrequency physical therapy group of allo-HSCT patients exhibited significantly less decline in muscle strength and functional capacity than the low-frequency physical therapy group [9].…”
Section: Physical Functioningcontrasting
confidence: 41%
See 2 more Smart Citations
“…Functional capacity was evaluated using the 6-min walk test, 50-foot walking time, and repeated sit-to-stand movement. While one study reported no significant increase in functional capacity after physical exercise intervention [24], several other studies described a significant increase in functional capacity among the physical exercise group compared to the control group, following physical exercise intervention [11,12,21,22]. In our study, we showed that the highfrequency physical therapy group of allo-HSCT patients exhibited significantly less decline in muscle strength and functional capacity than the low-frequency physical therapy group [9].…”
Section: Physical Functioningcontrasting
confidence: 41%
“…The onset timing of physical exercise intervention for allo-HSCT patients varies, and can occur in 1 of 3 phases: conditioning (before HSCT) [11][12][13][14][15][16][17], post engraftment (after HSCT) [18,19], or hospital discharge phase [20][21][22][23][24]. Recently, physical exercise intervention has reportedly been increasingly initiated during the conditioning phase (chemotherapy and radiation therapy regimen).…”
Section: Physical Exercise Intervention Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…The three studies that focused on exercise in an inpatient setting [4,5,14,21,33] showed that regular endurance training may not lead to an increase in endurance performance, but the loss of performance in the experimental groups was significantly lower than in control groups. Retrospective rehabilitation data analyzed by Morris et al [29] even did not show improvements in endurance performance either, whereas a subgroup of 40 % demonstrated improvement under glucocorticoid therapy. Non-randomized aerobic exercise intervention studies which started during the inpatient setting and were continued in the outpatient context, respectively, took place in the outpatient setting only, showed significantly enhanced endurance values in pre-/post-comparisons [7,13,18].…”
Section: Discussionmentioning
confidence: 91%
“…Studies have demonstrated the feasibility of VO 2peak measurement in survivors of allogeneic HCT, [15][16][17] and the potential benefit of exercise intervention in ameliorating functional decline. [18][19][20] These data suggest a role for investigating VO 2peak measurement (and potentially, multimodality intervention to improve functional capacity) before the anticipated physiological stress of HCT.…”
Section: Introductionmentioning
confidence: 99%